EVALUASI PELAKSANAAN INTERVENSI GIZI SPESIFIK PENURUNAN STUNTING PADA SASARAN REMAJA DIWILAYAH KERJA PUSKESMAS JATIBARANG KABUPATEN BEBES - Ziyadatul Chusna Almabruroh Yuni Alfi; Suci Utami; Rosmalia Kamil; Adi Irwansah (JURNAL KESEHATAN INDRA HUSADA, 2021)
The problem of stunting shows the influence of chronic nutritional problems starting from the condition of the mother/prospective mother, fetal period and infancy/toddler, as well as various diseases felt by children during toddlerhood. Therefore, it is necessary to make improvements such as in terms of prevention and direct reduction of disorders, namely with specific nutrition interventions and sensitive nutrition interventions. This type of research is descriptive analytic. The population is female teenagers totaling 140 people. The sampling technique used accidental sampling of 40 respondents. Data were obtained using a closed questionnaire. Analyzed using frequency distribution It was found that 40 young women (100%) had received information about the youth Posyandu but there were 26 young women (65%) who regularly attended the Posyandu. 25 young women (62.5%) did not take blood supplement tablets regularly. 37 young women (92.5) said they received counseling materials but 34 young women (85%) still consumed snacks like food sold on the roadside. Adolescent knowledge about anemia and stunting is good (85%) but 31 young women (77.5%) do not know that anemia can cause stunting. It is recommended that teenagers, especially young women, routinely consume blood-added tablets and participate in Youth Posyandu activities in order to avoid anemia and stunting